PREVALENCE OF FROZEN SHOULDER IN HYPERTENSIVE PATIENTS: A CROSS-SECTIONAL STUDY - Nabeel Yazdani; Asif Yousaf; Naeem Hussain; Syed Asif Ali; Mariam Zakia Chaudhari (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: To determine the prevalence of frozen shoulder in hypertensive patients and explore any correlation between hypertension and the development of frozen shoulder.Methods: This cross-sectional study was conducted on 220 hypertensive patients. Data collection included demographic information, medical history, and clinical examination for signs of frozen shoulder. The diagnosis was based on restricted shoulder movement and clinical criteria. Hypertension was confirmed through medical records and blood pressure measurements.Results: Out of the 220 hypertensive patients, 44 were diagnosed with frozen shoulder, giving a prevalence rate of 20%. The prevalence of frozen shoulder was significantly higher in hypertensive patients (20%) compared to the general population, where the estimated prevalence was around 5% (p-value = 0.02). Among the 44 patients with frozen shoulder, 25 (57%) had hypertension for more than 5 years, while 19 (43%) had hypertension for less than 5 years. A positive correlation (r = 0.65, p < 0.01) was observed between the duration of hypertension and the severity of frozen shoulder symptoms.Conclusion: The study concludes that the prevalence of frozen shoulder in hypertensive patients is significantly higher compared to the general population. The findings suggest that a longer duration of hypertension may be a contributing factor to the development and severity of a frozen shoulder.